The effect of cinnamomum cassia on two breast cancer cell lines / Sima Kianpour Rad - Kianpour Rad, Sima (2014)
The bark of the cinnamon tree (Cinnamomum cassia) is a popular culinary spice. It is also used in traditional medicine to maintain health and prevent disease. The antioxidant and anticancer activity of C. cassia was investigated using various assays. C. cassia bark was sequentially extracted with seven solvents of varying polarity. The acetone extract of C. cassia, at 30 μg/ml, protected the mouse fibroblast cell line, 3T3-L1, from DNA damage by 45 %, as estimated by the comet assay. The acetone extract had the highest total phenolic and flavonoid content. The hexane extract of C. cassia and the two main components, trans-cinnamaldehyde and coumarin, inhibited the proliferation of two breast cancer cell lines, the estrogen-sensitive MCF-7 cells (IC50, 34 ±3.52 μg/ml) and the estrogen-insensitive MDA-MB-231 cells (IC50, 32.42 ±0.37 μg/ml). The mechanism of cell death was investigated by determining the activity of the caspases. The expression of particular apoptotic genes such as Bcl2, Akt1, p53 and Bid were investigated by real time RT-PCR. The hexane extract activated initiator caspases-8 and -9 and effector caspases-3 and -7. There was up-regulation of Bid and p53 expression. Akt1 expression was down-regulated in MDA-MB-231cells but up-regulated in MCF-7 cells, indicating partial resistance to apoptosis. The activity of the antioxidant enzymes, catalase and glutathione peroxidase in both cell lines, in response to 100 μg/ml of hexane extract, decreased in a time dependent manner, whereas that of superoxide dismutase decreased in MDA-MB-231 cells but increased in MCF-7 cells, indicating that C. cassia bark is a good source of antioxidants. Together with its anticancer and anticarcinogenic properties, it is a good supplement for maintenance of health and prevention of cancer.